Answer
The solution to the system is:
- \( x = \frac{228}{43} \) (approximately 5.302)
- \( y = \frac{70}{43} \) (approximately 1.628)
Solution
It looks like you have the following system of linear equations:
**b)** \( 5x - 4y = 20 \)
**c)** \( 7x + 3y = 42 \)
Let's solve this system for the variables \( x \) and \( y \) using the **elimination method**.
### Step 1: Align the Equations
Write the equations one below the other for clarity:
\[
\begin{cases}
5x - 4y = 20 \quad \text{(Equation b)} \\
7x + 3y = 42 \quad \text{(Equation c)}
\end{cases}
\]
### Step 2: Make the Coefficients of \( y \) Opposites
To eliminate \( y \), we need the coefficients of \( y \) in both equations to be opposites.
- **Multiply Equation b by 3:**
\( 5x \times 3 - 4y \times 3 = 20 \times 3 \)
\( 15x - 12y = 60 \)
\(\quad\) **(Equation b1)**
- **Multiply Equation c by 4:**
\( 7x \times 4 + 3y \times 4 = 42 \times 4 \)
\( 28x + 12y = 168 \)
\(\quad\) **(Equation c1)**
### Step 3: Add the Modified Equations
Add **Equation b1** and **Equation c1** to eliminate \( y \):
\[
15x - 12y + 28x + 12y = 60 + 168
\]
\[
43x = 228
\]
\[
x = \frac{228}{43} = 5.\overline{3023} \quad \text{or} \quad 5 \frac{13}{43}
\]
### Step 4: Substitute \( x \) Back into One of the Original Equations
Let's use **Equation b** to find \( y \):
\[
5x - 4y = 20
\]
\[
5\left(\frac{228}{43}\right) - 4y = 20
\]
\[
\frac{1140}{43} - 4y = 20
\]
\[
-4y = 20 - \frac{1140}{43}
\]
\[
-4y = \frac{860}{43} - \frac{1140}{43}
\]
\[
-4y = \frac{-280}{43}
\]
\[
y = \frac{-280}{43} \div -4 = \frac{70}{43} = 1.\overline{6279} \quad \text{or} \quad 1 \frac{27}{43}
\]
### **Solution:**
\[
x = \frac{228}{43} = 5 \frac{13}{43} \quad \text{(approximately 5.302)}
\]
\[
y = \frac{70}{43} = 1 \frac{27}{43} \quad \text{(approximately 1.628)}
\]
---
**Final Answer:**
The solution to the system is
x = 228⁄43 (which is 5 13⁄43)
and
y = 70⁄43 (which is 1 27⁄43).
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution